2017
DOI: 10.1109/tcbb.2016.2591549
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Transductive Spectral Clustering Methods in a Military Medical Concussion Database

Abstract: Traumatic brain injury (TBI) is one of the most common forms of neurotrauma that has affected more than 250,000 military service members over the last decade alone. While in battle, service members who experience TBI are at significant risk for the development of normal TBI symptoms, as well as risk for the development of psychological disorders such as Post-Traumatic Stress Disorder (PTSD). As such, these service members often require intense bouts of medication and therapy in order to resume full return-to-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…7,8 For example, we recently developed a graph theoretical model to predict an increase/decrease in symptomology based on medications prescribed prior to injury and neuropsychological testing conducted upon a patient’s visit to a clinic after injury. 9 In this work, we showed that such a model can reliably outperform other parametrically and/or machine-learning-based models in terms of predicting patient outcomes.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…7,8 For example, we recently developed a graph theoretical model to predict an increase/decrease in symptomology based on medications prescribed prior to injury and neuropsychological testing conducted upon a patient’s visit to a clinic after injury. 9 In this work, we showed that such a model can reliably outperform other parametrically and/or machine-learning-based models in terms of predicting patient outcomes.…”
Section: Introductionmentioning
confidence: 83%
“…Using CSP, we previously showed how a graph-based representation can be more effective in terms of classification accuracy for a small (sparsely labeled) dataset. 9 However, this work was limited in that the graph-based structure failed to identify how information propagates from one region of the graph (i.e., cluster of nodes) to another separate region. Therefore, in this paper we sought to extend our previous work by demonstrating the manner in which CSP classifies symptomology.…”
Section: Introductionmentioning
confidence: 99%
“…The models used in military training are based on data processing and are becoming increasingly common in military training [68]. In relation to body negative pressure, we found evidence from algorithm-supported studies on military data that focus on military medical studies [67].…”
Section: Military Medical Studiesmentioning
confidence: 89%
“…In this category, we include the themes body negative pressure and training. In relation to body negative pressure, we found evidence from algorithm-supported studies on military data that focus on military medical studies [67].…”
Section: Military Medical Studiesmentioning
confidence: 90%